An insight into Verbascum bombyciferum extracts: Different extraction methodologies, biological abilities and chemical profiles - Angeloni, Simone; Zengin, Gokhan; Sinan, Kouadio Ibrahim; Ak, Gunes; Maggi, Filippo; Caprioli, Giovanni; Mahomoodally, Mohamad Fawzi (Elsevier, 2021)
The genus Verbascum, commonly known as mullein, bears several species traditionally used to treat various infections, inflammations and wounds. In this study, extracts from V. bombyciferum, an endemic Verbascum species from Turkey, obtained by different solvents and extraction techniques, were investigated for their bioactive contents using spectrophotometry and high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) and evaluated for their antioxidant, as well as enzyme inhibitory potentials. While spectrophotometric determination revealed the homogenizer assisted extraction/methanolic extract to yield the highest total phenolic and flavonoid contents (41.80 +/- 0.70 mg GAE/g and 39.44 +/- 0.30 mg RE/g, respectively), the most significant total bioactive compounds (polyphenols) in the amount of 272.862 mg kg(-1), established by HPLC-MS/MS analysis, was noted for the maceration/methanolic extract. Overall, the extracts showed varied antioxidant potency, displaying free radical scavenging ability (DPPH assay: 1.04-51.33 mg TE/g; ABTS assay: 80.04-85.60 mg TE/g), reducing power (CUPRAC: 51.48-183.26 mg TE/g; FRAP: 36.33-90.04 mg TE/g; metal chelating activity (18.48-19.80 mg EDTAE/g) and total antioxidant capacity (phosphomolybdenum assay: 0.78-1.92 mmol TE/g). However, extract of homogenizer assisted extraction/methanol exhibited the highest antioxidant activity in most assays. Only the maceration/methanolic extract inhibited all the studied enzymes (acetylcholinetserase: 2.02 +/- 0.20 mg GALAE/g; butyrylcholinesterase: 4.57 +/- 0.09 mg GALAE/g; tymsinase 21.44 +/- 3.41 mg KAE/g and amylase: 0.46 +/- 0.01 mmol ACAE/g). This study is the first attempt to highlight the potential industrial applications of the endemic plant V. bombyciferum, as a natural source of bioactive compounds that could be considered for future development of phytopharmaceuticals, targeting specific oxidative stress-linked diseases including diabetes, skin hyperpigmentation, and neurological disorders.
Keywords: Verbascum bombyciferum; Polyphenols; Antioxidant; Enzyme inhibition; Phytopharmaceutics